MODEL GAYA BERTUTUR PENGHUNI DI APARTEMEN BERSUBSIDI: SUATU KAJIAN SOSIOPRAGMATIK “ALIH KODE” - Rosida Tiurma Manurung (Fakultas Seni Rupa dan Desain ITB, 2010)
Language serves as a means of communication and interaction in society. It functions if the language has a meaning. The language will have particular sense if it has a context. In this term the context is divided into two: context of situation and context of culture. An act sequence can be well understood and obvious if it has the context of situation and the context of socio-cultural in which language is used. The context of situation is a place where the speech is expressed directly. An apartment is a residence located on one floor of multistory buildings that has its own particularities in its position as the context of the situation. Based on the observations, tenants of subsidized apartment come from different level of social, economic, and culture, which apparently have their own style of speaking. The primary focus of this research is the speaking styles of apartment tenants who come into contact with the language with all forms of language events as a result. Study approach of the research is socio-pragmatic study. The reason for using socio-pragmatic study is that the act sequence has a social function as a means of communication and it is used to identify a social group as well as the act sequence itself is a pragmatic social interaction. Tenants arising from different socio-culture and behavior perform their typical characteristics of speaking style. In this research, the existence of code switching between Indonesian and English was found. The phenomenon of code switching appears because of the influence of science, technology and telecommunication advances and the globalization era. Code switching becomes the speaking styles among apartment tenants, which are more and more flourishing. Keywords: speaking style, tenants of subsidized apartment, code switching, socio-pragmatic